Regulating the Sixth Sense: The Growing Need for Forward-Looking Data Privacy and Device Security Policy as Illustrated by Brain-Computer Interfaces - Hannah Gallagher (Washington University Journal of Law & Policy, 2021)
Many of today’s consumers are skeptical of the vast amounts of information technology companies are capable of gathering. Methods of collecting such data have become more invasive over time and have the potential to become compromised or abused. Gallagher urges policymakers to consider the regulations necessary to address privacy and security risks associated with emerging biotechnology such as brain-computer interfaces (“BCI”) without disrupting innovation incentives.This Note analyzes the current state of augmentative BCI technology, the trend of increasingly invasive technology, and proposed policy solutions for governing data privacy. Since BCIs will be collecting data on consumers’ neural signals, accessing their most private thoughts and emotions, the need for adequate data privacy protections is urgent. This Note details elements of a proposed solution including a broad statute equipping an agency to develop adaptable regulations, sufficient enforcement mechanisms, device security standards, and a potential prohibition on collection of certain data types.
Keywords: information technology; IT; technology; device; device security; data privacy; privacy; data security; security; data; collection; data collection; invasive; policy; regulation; brain-computer interface; brain-computer interfaces; BCI